Analisis Manajemen Resiko Keuangan Pada UMKM Batik Pancor Emas - Nuriyah, Leny Syafiatun (Universitas Bumigora, 2026)
The existence of UMKM suppresses economic growth in Indonesia, UMKM are businesses founded by individuals that support the community's economy with the power to grow the economy. UMKM have a large contribution and a major role in the current economy, but in a business there will always be problems or risks that will arise at any time in a business. Risks can be anticipated with risk management. The purpose of this study is to analyze financial risk management, especially in financial management that occurs inUMKM, financial management has an important influence on business growth both on a large and small scale, financial performance is a determinant of the success of a business, so this study is expected to find out the application and understanding of what financial management is applied by UMKM actors. The subject of this study is the Batik Pancor Emas UMKM with a qualitative research method. Good financial management in a business can minimize existing risks.